Strategi Pembelajaran Al Islam pada Masa Pandemi Covid-19 di SD Muhammadiyah 1 Kota Bandar Lampung - Najah, Isma Nurun; Fakhri, Jamal; Akmansyah, Muhammad; Syafe’i, Imam (CV. Creative Tugu Pena, 2022)
Covid-19 first appeared in Indonesia in March 2020 which had a wide impact on all sectors of life, including education.Adaptation and innovation are necessary to face the conditions of the new learning model, namely distance learning. In dealing with this, educational institutions are required to provide solutive learning strategies, in accordance with existing conditions, as well as SD Muhammadiyah 1 Bandar Lampung. This study aims to analyze Al-Islam learning strategy during pandemic at SD Muhammadiyah 1 Bandar Lampung. This research focuses on three problems, namely: 1) Learning organization strategy, 2) Learning delivery strategy, 3) Learning management strategy. The research method used in this study is to use qualitative research methods and the type of research uses descriptive qualitative, for data collection using observation, documentation and interviews, while in analyzing the data using data reduction, data presentation, and drawing conclusions. The results of the study are 1) Al-Islam learning organization strategy, namely through ISMUBA guidelines which are implemented into lesson plans by learning through RubelMu. 2) Learning delivery strategy content through the use of RubelMu media which is designed in such a way by Muhammadiyah during online learning due to covid-19 which is proven to be structured, effective and efficient. 3) Learning management strategies are through scheduling making of videos according to the learning material, providing learning notes through concept of daily grades and student test scores, managing motivation through conveying the urgency of understanding the material, and controlling student learning through giving assignments to be do at home. So that the learning strategy during the COVID-19 pandemic using the RubelMu media was considered appropriate and influential for PAI learning at SD Muhammadiyah 1 Bandar Lampung City. Keywords: Learning Strategy, Learning Organization Strategy, Learning Management Strategy